(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical features of liver injury and evaluate treatment outcomes in adult dengue patients at Vietnam Transport Hospital. Methods: A retrospective cross-sectional study was conducted on 89 patients aged ≥18 years, diagnosed with dengue fever (positive NS1 or IgM Dengue), admitted between June and November 2023. Patients with chronic liver disease, hematologic disorders, hepatotoxic drug use, or admission after day 6 of illness were excluded. Clinical and laboratory data were collected and analyzed. Results: Right upper quadrant pain occurred in 23.6%, hepatomegaly in 5.6%, jaundice in 1.1%, and no hepatic encephalopathy was recorded. AST and ALT elevations were mostly mild–moderate: AST 2–5×ULN (31.5%), 5–15×ULN (61.8%); ALT 2–5×ULN (55.1%), 5–15×ULN (37.1%). Hyperbilirubinemia (>17 µmol/L) was found in 2.2% and PT% <70 in 1.1%. Mean hospital stay was 5.1 days; 96.6% recovered with no deaths. Conclusion: Liver injury in dengue fever is mainly characterized by mild–moderate transaminase elevation, with rare cholestasis and coagulopathy. Recovery rate was high, with an average hospital stay of 5 days.